YouTube – An unreliable source of information for Total hip replacement - Yadav, Amit Kumar (J Clin Orthop Trauma, 2020)
BACKGROUND: YouTube is now becoming important for people as a source of health related information. The aim of the present study was to assess the educational quality of YouTube videos related to Total hip replacement. METHODS: A search on YouTube for the term “Total hip replacement” was performed. Data from 47 most relevant videos were collected. Quality assessment checklists with a scale of 0–10 points were developed to evaluate the video content. Videos were grouped into poor quality (grade 0–3), acceptable quality (grade 4–7), and excellent quality (grade 8–10). RESULTS: 91% of videos were of poor educational quality (43/47), 9% were of acceptable quality (4/47) and none of the videos were of excellent quality. Common missing information was regarding non-operative treatment options and types of bearing surfaces. CONCLUSIONS: Videos regarding total hip replacement are frequently viewed on YouTube which is an unreliable educational source for patients, so it is important that surgeons should have knowledge about the available content so as to direct our patients to a suitable source. Also, surgeons should upload more informative videos that can be understood by patients which will be beneficial in providing information and education regarding Total Hip Replacement.